The level of entrepreneurial intention among student of science and technology of physical and sport activities: comparative study at the institute of Biskra. - صواش عيسى; دحية خالد (sports creativity, 2025)
The following study aims to know the level of entrepreneurial intention among students of science and technology of physical and sports activities at Biskra University. This is in addition to identifying the significance of the differences in the entrepreneurial orientation according to the academic specialization variable such as sports training, school sports activity, management of sports infrastructure and human resources. The study adopts the comparative method, where the research tool is a questionnaire designed for this purpose consisting of 30 statements distributed on 4 axes: self-intention, awareness of incentives and obstacles to entrepreneurial work, entrepreneurial education, and entrepreneurial spirit. The questionnaire is distributed to a random sample of 52 students in the second master's and first-year PhD levels at the Institute. It was concluded that students of science and technology of physical and sports activities have a high tendency towards entrepreneurial work. Moreover, there are no statistically significant differences in entrepreneurial intention among students attributed to the variable of academic specialization as well as the variable of academic level.